The Students’ Anxiety Factors in Speaking English at SMAN 8 Pinrang - Asdar, Nur Aulia; Dollah, Syarifuddin; Farahdiba, Syarifah (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
This research aims (1) to find out the internal factors that cause the students’ anxiety in English speaking classroom, and (2) to find out the external factors that cause the students’ anxiety in English speaking classroom. In this study, the researcher used a qualitative method with a case study approach. Three perceived-anxious students were selected as the subject of this research interview. The data were gathered through interviews and an observation checklist. The result of the study showed two factors, they are internal factors (fear of mistakes, shyness, lack of confidence, lack of motivation) and external factors (embarrassment, limited vocabulary, grammatical errors, friends or classmates, lack of preparation). These findings suggest that the teacher should be more aware of students’ anxiety to raise students’ motivation to speak up confidently and fluently in an English-speaking class. As such, teachers are urged to be fairly creative in devising better techniques that could encourage the students to speak more. Finally, teachers should also provide materials that contribute to students’ vocabularies and confidence, so that the students have a better performance in speaking English in the future.